Cairo to Constantinople Francis Bedford's Photographs of the Middle East - Bedford, Francis 1816-1894; Gordon, Sophie (Royal Collection Trust, 2013)
In 1862 the leading British photographer Francis Bedford was commissioned by Queen Victoria to accompany her son and heir, the future King Edward VII, on an ambitious journey around the Middle East. This book documents that journey